New light on the early urbanisation of Copenhagen: with the Metro Cityring excavation at Rådhuspladsen (Town Hall square) as a point of departure - Dahlström, Hanna (Danish Journal of Archaeology, 2013)
Copenhagen’s origin and early development have long been subject to study, and has since the nineteenth century resulted in numerous and sometimes conflicting theories. The dearth of large excavations in the old parts of the city in modern times has resulted in fragmentary archaeological evidence and a concomitant lack of synthesis of a more modern nature. In connection with the current, large-scale, excavations connected to the Metro Cityring project (2009–), the Museum of Copenhagen has had the opportunity to conduct major excavations pertinent to the development of the medieval town. The site at Rådhuspladsen (the Town Hall Square) lies on the borders of the high and late medieval town, but in an area traditionally seen as located outside the earliest settlement. The preliminary results from this excavation, together with indications from excavations and watching briefs in recent years, enable us to update our hitherto knowledge and beliefs about the origins of Copenhagen. The discovery of a previously unknown cemetery at Rådhuspladsen, together with a large number of pits and wells backfilled with household refuse and waste from iron working, yields new information on the activities in the early town, and perhaps also clues to the organisation and power structure of the town’s early phase. This article sketches in broad outline the early medieval findings from Rådhuspladsen as well as some of the recent years’ archaeological observations from around the city centre. Together, these form the background for a discussion on the organisation and character of Copenhagen in the early medieval period, and some preliminary hypotheses concerning the urbanisation process of the city.